Temperament Types at Age 3 and Smartphone Overdependence at Age 10 - Kim, Yeon Ha (Frontiers in Psychology, 2022)
Few studies have addressed the longitudinal links between early temperament types and later problematic smartphone use. This study aims to identify children’s early temperament types at age 3 and to examine the link between the temperament types and smartphone overdependence at age 10. This study utilized a population-based data set presented by the Panel Study on Korean Children. Based on emotionality, activity, and sociability levels at age 3, children were clustered into similar temperament types. Links between the early temperament types and the risks of smartphone overdependence at age 10 were identified through analyses of covariances and binary logistic regressions. Three early temperament types were identified among Korean children: reactive (28.1%), sociable (37.2%), and cautious (34.8%). Children’s smartphone dependence at age 10 differed according to the temperament types identified at age 3. Compared to children with the sociable temperament type, children with the reactive type or the cautious type had an increased risk of smartphone overdependence. The link between temperament types at age 3 and smartphone overdependence at age 10 was meaningful. Cautious children were the most vulnerable group to the risk of smartphone overdependence. Temperament type identification in early years may be a useful measure for screening groups of children who are at risk for problematic smartphone use and need proactive interventions.